The Effect of YouTube on Students’ Listening Comprehension in Millenial Era - Hafizhah, Azzahra amy; Hasan, Jhems Richard (Journal of English Teaching and Linguistic Issues (JETLI), 2023)
This study investigates the effect of learning with YouTube, particularly on students' listening comprehension. This is quantitative research. In addition to using an ex post facto design, the form of observation also employed an ex post facto design. This study employed pre-test and post-test methodologies to pre-test the final outcomes of acquiring listening comprehension using YouTube. For the post-test, namely by using a questionnaire. The study samples were collected through the distribution of questionnaires. The samples consisted of 20 eighth-semester IAIN Sultan Amai Gorontalo students. This study's samples used only one class. This study's findings revealed that a significance value of 0.05% = 0.05 was less than 0.05 (sig. 0.000 0.05). Therefore, 0.5 H0 was rejected, whereas H1 was accepted. The results indicated that YouTube impacted the auditory comprehension of eighth-semester English students at IAIN Sultan Amai Gorontalo during the 2020–2021 academic year.